IMPLEMENTASI PERATURAN BUPATI KUTAI KARTANEGARA NOMOR 36 TAHUN 2013 TENTANG PENYELENGGARAAN ADMINISTRASI PENGUASAAN TANAH ATAS TANAH NEGARA DI KECAMATAN TENGGARONG KABUPATEN KUTAI KARTANEGARA - Herjunita, Rizka (Jurnal Paradigma, 2026)
The purpose of this research is to gain a deeper understanding of how the Kutai Kartanegara Regent's Regulation Number 36 of 2013 concerning Administration of Land Tenure over State Land is implemented in Tenggarong District, Kutai Kartanegara Regency. This study focuses on the aspects of Communication, Resources, Disposition, Bureaucratic Structure, as well as supporting and inhibiting factors in the implementation of the Kutai Kartanegara Regent's Regulation Number 36 of 2013 in Tenggarong District, Kutai Kartanegara Regency. The research method used is descriptive research with a qualitative approach and interactive data analysis.To collect data, this study used various techniques, including literature studies, field research, and interviews with the aim of obtaining accurate information according to the needs of researchers in this study. Factors supporting the successful implementation of Kutai Kartanegara Regent Regulation Number 36 of 2013 include the existence of a legal basis and clear technical guidelines, implementation according to applicable technical guidelines and standard procedures, as well as the use of effective measurement technology such as GPS, the compass method to determine coordinates. , land area calculator application, and manual meter use. However, there are also inhibiting factors in the implementation of this regulation, including socialization that is not optimal, limited measurement tools, limited operational funds, and lack of adequate human resources.Keywords: Implementation of Regent Regulations, Certificate of Land Ownership.